PENGARUH KOMPENSASI TERHADAP KINERJA DOSEN FKIP UNIVERSITAS RIAU - Syabrus, Hardisem; ', Ester; ', Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The aims of this research is to determine the effect of compensation on faculty performance FKIP Riau University. The population in this research were 222 lecturers. The sample size as many as 69 people by using proportional stratified. Collecting data in this study using techniques of documentation. Performance data obtained from the document Targets Employee Work and work behavior lecturer at the office each department FKIP Riau University lecturers, while the compensation data obtained from the financial part of the rector of Riau University. The results of this study indicate that compensation is positive and significant effect on the performance of lecturers FKIP Riau University.Key Words: compensation, performance, salary, allowance